Exploring the attitudes and expectations of English major students towards phonetics - Trịnh Thị Thủy (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Khoa học Xã hội, 2024)
Phonetics is challenging for most learners, yet research in this area is limited at Vietnamese universities. This study seeks to understand the expectations and attitudes of English major students toward phonetics learning and teaching at a university in Hanoi. The study involved fifty second-year English majors. A survey was conducted using a questionnaire that covered 08 different topics within the phonetics course over two semesters, along with a closed questionnaire comprising 25 questions to gauge the students’ perspectives on English phonetics. Findings indicated that students favored segmental aspects over suprasegmental ones. Moreover, the survey revealed that students had a positive outlook on learning phonetics and felt that the subject had improved their English pronunciation. Lastly, students had specific expectations for phonetics instruction, including the desire for instructors to use various methods and activities in lessons, provide more practice exercises, and incorporate technology into phonetics teaching and learning.